The Impact of a Virtual Orthopaedic Surgery Symposium on Medical Students: Increasing Awareness and Knowledge of the Field. Issue 4 (29th October 2022) - Quan, Theodore; Gu, Alex; Agarwal, Amil R.; Bernstein, Simone A.; Malyavko, Alisa; Levine, William N.; Cannada, Lisa K.; ,
Abstract : Background: Orthopaedic surgery has become an increasingly popular field of residency training for medical students. Many institutions offer elective time to explore areas of interest through clinical rotations and research; however, most of these opportunities are reserved for senior medical students. The purpose of this study was to evaluate the impact of a dedicated medical student orthopaedic surgery symposium to increase awareness about the field and to assess students' interest and knowledge of orthopaedic surgery before and after the symposium. Methods: Medical students were invited to submit orthopaedic surgery–related research to a free, 1-day virtual symposium held in April 2022. Abstracts were reviewed and selected from 9 different orthopaedic surgery subspecialty categories. Survey assessments were sent to medical students to complete before and after the symposium. The surveys included questions related to participant demographics as well as interest and knowledge about the field of orthopaedic surgery. Statistical analyses were completed to compare the participants' responses before and after the symposium. Results: In total, 962 medical students registered for the 4-hour symposium. Of these, 58.5% completed the presymposium survey and 48.0% completed the postsymposium survey. 13.3% of the respondents reported being "very knowledgeable" about the various orthopaedic surgery subspecialties before the symposium, which increased to 18.4% after the symposium. 46.9% of the participants stated that they were "knowledgeable" about the daily life of an orthopaedic surgery resident before the symposium, which increased to 67.3% after the symposium. Similarly, the percentage of respondents who reported that they were "very knowledgeable" about the residency match process increased from 12.2% presymposium to 22.4% postsymposium. Conclusions: As interest in pursuing a career in orthopaedic surgery increases, medical students will continue to seek information, mentorship, and opportunities to present their research in preparation for residency applications. Our study demonstrated that a large-scale, national, virtual orthopaedic surgery symposium provided a platform to augment medical students' knowledge of the field, present their research, and interact with faculty members. Level of Evidence: Level V.